Stress and stiffness as predictors of shear wave velocity in peripheral nerve. - Chelsea L Rugel; Seth D Thompson; Colin K Franz; C J Heckman; Mitra Lavasani; Sabrina S M Lee (PLoS ONE)
Shear wave elastography (SWE) is a promising non-invasive indicator for diagnosing peripheral neuropathy. Emerging validation studies using ultrasound-based measures of shear wave velocity (SWV) in other biological tissues, such as muscle, demonstrate there is a concern of whether SWE is an accurate measure of tensile stress or stiffness. Distinguishing between these two parameters and their relationship with SWV is crucial if SWE is to be used as a biomarker for peripheral neuropathies, where changes in mechanical properties are known to occur. In this study, we use cat sciatic nerves to first evaluate SWV in situ at knee positions known to reduce (90° flexion) or increase (180° extension) stress, and then excise nerves to directly quantify the relationships between SWV, stress, and stiffness with ex vivo tensile testing. Our ex vivo findings show that although SWV can be predicted using either stress or stiffness, stress explains more variability in sciatic nerve SWV. However, while stress remains the better predictor of SWV ex vivo, within the SWV range established in situ, stiffness improves its accuracy at estimating SWV, especially when also accounting for factors related to nerve viscoelasticity. Therefore, if SWE is to be used in clinical settings as an indicator of nerve stiffness in peripheral neuropathy, it is essential to standardize parameters such as limb positioning and nerve preloading, which could potentially mask pathological changes in nerve stiffness.